2021
DOI: 10.1002/adom.202002058
|View full text |Cite
|
Sign up to set email alerts
|

Organic Permeable Base Transistors – Insights and Perspectives

Abstract: Vertical organic transistors have emerged as a new device concept holding great promise to overcome the limitations of lateral organic transistors. In this regard, the organic permeable base transistor (OPBT), a special kind of vertical transistor, stands out due to excellent performance figures such as low‐voltage operation and high transition frequency measured in a pulse‐biasing mode. On the occasion of Prof. Karl Leo's 60th birthday, his contributions to the development of high‐performance OPBTs are honore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 11 publications
(12 citation statements)
references
References 55 publications
0
12
0
Order By: Relevance
“…DPh-DNTT thin-films is exceptionally low in comparison to thin-films of other organic semiconductors, making DPh-DNTT potentially relevant also for vertical transistors, such as OPBTs. [7,47]…”
Section: Low-voltage Organic Tfts Using a Thin Gate Dielectricmentioning
confidence: 99%
See 2 more Smart Citations
“…DPh-DNTT thin-films is exceptionally low in comparison to thin-films of other organic semiconductors, making DPh-DNTT potentially relevant also for vertical transistors, such as OPBTs. [7,47]…”
Section: Low-voltage Organic Tfts Using a Thin Gate Dielectricmentioning
confidence: 99%
“…This potentially indicates that the vertical access resistance component from the vacuum‐deposited polycrystalline DPh‐DNTT thin‐films is exceptionally low in comparison to thin‐films of other organic semiconductors, making DPh‐DNTT potentially relevant also for vertical transistors, such as OPBTs. [ 7,47 ]…”
Section: Survey Of Organic Transistors Showing Rcw mentioning
confidence: 99%
See 1 more Smart Citation
“…Compared to SBVTs and MISVTs, SCLVTs display the unique advantage of combining low operating voltages and high operating speeds. 59,77–79 By incorporating a SCLVTs and an OLED into a single device, Wu et al demonstrated an OLET with a permeable base emitting the three primary colors. 80 A schematic cross-section of the VOLET structure indicating the material used for each primary color is depicted in Fig.…”
Section: Electronic and Photonic Applicationsmentioning
confidence: 99%
“…Furthermore, the function of the devices crucially relies on the thin, permeable base electrode and its fabrication is still one of the main challenges. [26,27] The second promising concept, the vertical organic field-effect transistor, resembles a lateral transistor in its device. The gate electrode is located underneath the source electrode and not between the source and drain electrodes.…”
Section: Introductionmentioning
confidence: 99%